A Short Review on Ni Based Catalysts and Related Engineering Issues for Methane Steam Reforming - Eugenio Meloni (Catalysts, 2020)
Hydrogen is an important raw material in chemical industries, and the steam reforming of light hydrocarbons (such as methane) is the most used process for its production. In this process, the use of a catalyst is mandatory and, if compared to precious metal-based catalysts, Ni-based catalysts assure an acceptable high activity and a lower cost. The aim of a distributed hydrogen production, for example, through an on-site type hydrogen station, is only reachable if a novel reforming system is developed, with some unique properties that are not present in the large-scale reforming system. These properties include, among the others, (i) daily startup and shutdown (DSS) operation ability, (ii) rapid response to load fluctuation, (iii) compactness of device, and (iv) excellent thermal exchange. In this sense, the catalyst has an important role. There is vast amount of information in the literature regarding the performance of catalysts in methane steam reforming. In this short review, an overview on the most recent advances in Ni based catalysts for methane steam reforming is given, also regarding the use of innovative structured catalysts.